Pendidikan Karakter Berbasis Kearifan Lokal: Signifikansi Edukatif dalian Na Tolu bagi Remaja di Mandailing Natal - Ahmad Asrin; Rohman; Khairul Fuadi (Fakultas Tarbiyah dan Kegurusn Universitas Islam Bandung, 2025)
This study analyzes the educational significance of the Dalian Na Tolu tradition as a form of local wisdom in fostering youth character in Mandailing Natal. As a socio-cultural system that structures the relationships between mora (wife givers), kahanggi (patrilineal relatives), and anak boru (wife receivers), this tradition is transmitted across generations through customary practices and daily social interactions. Employing a descriptive qualitative approach, data were collected through interviews, participant observation, and document analysis in four villages: Panyabungan Julu, Tolang, Pagur, and Simpang Tolang. The findings reveal that Dalian Na Tolu plays a strategic role in instilling core character values such as respect, compassion, solidarity, mutual cooperation, and deliberation, which align with modern character education principles and Islamic teachings. Revitalization efforts are carried out through collaboration between traditional and religious leaders, youth activities under Naposo Nauli Bulung, cultural training, and daily practice. The study recommends integrating Dalian Na Tolu values into formal and non-formal education, as well as utilizing digital media to strengthen youth character development in the era of globalization.